Screenwriting creative labor and professional practice - Conor, Bridget 1980- (Routledge, Taylor & Francis Group, 2014)
"Screenwriting has been the subject of a wealth of popular literature that seeks to offer this work to all, to reveal the 'secrets' of screenwriting or to provide accounts of how to succeed in the mainstream screen production industries, primarily in Hollywood. But the deluge of How-to style manuals and interview collections offer little systematic analysis of the histories, practices, identities and subjects which form and shape the daily working lives of screenwriters. Screenwriting work demands particular and complex forms of subjectivity in order to distinguish it from other forms of filmmaking and writing, to make the work knowable and do-able. This book analyzes the ways in which screenwriters navigate and make sense of the labor markets in which they are immersed. Drawing on historical and critical perspectives of mainstream screenwriting in the USA and UK, as well as empirical data drawn from interviews, labour market and textual analysis, this book presents an original and multi-faceted case study of screenwriting as creative labor and professional practice. Using a range of theoretical approaches and an interdisciplinary methodological framework, it examines both the structural and subjective features of screenwriting work and it analyzes not only who has access to the work, but also who is excluded from this profession"--